Florida Invader: Reticulated Python - Steve A. Johnson; Monica McGarrity (EDIS)
WEC294, a 2-page illustrated fact sheet by Steve Johnson and Monica McGarrity, describes this native to southeastern Asia, which has been found in the wild but is not established in Florida, and explains how to identify and report sightings. Published by the UF Department of Wildlife Ecology and Conservation, August 2010.